2022
DOI: 10.1155/2022/5334095
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Hepatocellular Carcinoma and Intrahepatic Cholangiocarcinoma Based on Radiomic Analysis

Abstract: Introduction. Considering the narrow window of surgery, early diagnosis of liver cancer is still a fundamental issue to explore. Hepatocellular carcinoma (HCC) and intrahepatic cholangiocarcinoma (ICCA) are considered as two different types of liver cancer because of their distinct pathogenesis, pathological features, prognosis, and responses to adjuvant therapies. Qualitative analysis of image is not enough to make a discrimination of liver cancer, especially early-stage HCC or ICCA. Methods. This retrospecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…Their symptoms, serum tumor markers, and imaging manifestations have differences as well as similarities. Although it has been reported that radiologic diagnostic models based on CT and MRI images can rapidly differentiate HCC from ICCA [ 3 , 4 ], especially noncontrast MRI which is difficult for radiologists to correctly distinguish them accordingly, so far, there is no relevant literature report on noncontrast MRI based on T2 βˆ— WI to differentiate ICCA from HCC. Therefore, it would be of great benefit to both doctors and patients to discover a method to identify different types of primary hepatic carcinoma on non-contrast-enhanced MRI scans.…”
Section: Introductionmentioning
confidence: 99%
“…Their symptoms, serum tumor markers, and imaging manifestations have differences as well as similarities. Although it has been reported that radiologic diagnostic models based on CT and MRI images can rapidly differentiate HCC from ICCA [ 3 , 4 ], especially noncontrast MRI which is difficult for radiologists to correctly distinguish them accordingly, so far, there is no relevant literature report on noncontrast MRI based on T2 βˆ— WI to differentiate ICCA from HCC. Therefore, it would be of great benefit to both doctors and patients to discover a method to identify different types of primary hepatic carcinoma on non-contrast-enhanced MRI scans.…”
Section: Introductionmentioning
confidence: 99%
“…Qualitative image analysis is not sufficient to differentiate between HCC or ICC. Xu et al ( 48 ). developed a diagnostic model based on CT images to provide a reference for future differential diagnosis of HCC and ICC.…”
Section: Application Of Conventional Radiomics In Intrahepatic Cholan...mentioning
confidence: 99%
“…Thus, these techniques can present a challenge in poor-resource settings. The experience level of radiologists could also compromise the accuracy of diagnosis and the frequency of misdiagnoses [58].…”
Section: Plos Onementioning
confidence: 99%